1988
DOI: 10.1007/bf01907549
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-activated ion channels in smooth muscle: a mechanism for the initiation of stretch-induced contraction

Abstract: As in many smooth muscle tissue preparations, single smooth muscle cells freshly dissociated from the stomach of the toad Bufo marinus contract when stretched. Stretch-activated channels have been identified in these cells using patch-clamp techniques. In both cell-attached and excised inside-out patches, the probability of the channel being open (Po) increases when the membrane is stretched by applying negative pressure to the extracellular surface through the patch pipette. The increase in Po is mainly due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
129
2
4

Year Published

1990
1990
2002
2002

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(146 citation statements)
references
References 39 publications
11
129
2
4
Order By: Relevance
“…Kleinhaus & Kao (1969) (Nakayama & Tanaka, 1993 Ca2P channels (Kirber et at. 1988;Meininger & Davis, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kleinhaus & Kao (1969) (Nakayama & Tanaka, 1993 Ca2P channels (Kirber et at. 1988;Meininger & Davis, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…SA channel activities were first reported by Guharay & Sachs (1984) in cultured embryonic chick skeletal muscle cells. Later, they were found in many other types of cells: oocytes and red blood cells (Yang & Sachs, 1987;, lens epithelial cells (Cooper, Tang, Rae & Eisenberg, 1986), hair cells (Ohmori, 1984;Hudspeth, 1985) and smooth muscle cells (Kirber, Walsh & Singer, 1988;Hisada, Ordway, Kirber, Singer & Walsh, 1991;Wellner & Isenberg, 1993). It has been shown that the inward currents flowing through SA channels tend to depolarize the cell.…”
mentioning
confidence: 99%
“…SACs were activated by applying negative pressure (suction) to the back end of the patch pipette as described previously (4,8). The single-channel unitary currents were recorded with an Axopatch-1D amplifier (Axon Instruments, Foster City, CA), using the cell-attached patch configuration of the patch-clamp technique.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3]. SACs in smooth muscle have also been shown to be Ca 2ϩ permeable (4)(5)(6). This conclusion was obtained from patch-clamp ion substitution experiments where Ca 2ϩ was the only available carrier of the inward current.…”
mentioning
confidence: 99%
See 1 more Smart Citation